Electrosprayed alginate nanoparticles as CRISPR Plasmid DNA delivery carrier: preparation, optimization, and characterization - Alallam, Batoul; Altahhan, Sara; Taher, Muhammad; Mohd Nasir, Mohd Hamzah; Abd Almonem, Doolaanea (MDPI, 2020)
Therapeutic gene editing is becoming more feasible with the emergence of the Clustered Regularly Interspaced Short Palindromic Repeats (CRISPR)/CRISPR-associated protein (Cas) system. However, the successful implementation of CRISPR/Cas9-based therapeutics requires a safe and efficient in vivo delivery of the CRISPR components, which remains challenging. This study presents successful preparation, optimization, and characterization of alginate nanoparticles (ALG NPs), loaded with two CRISPR plasmids, using electrospray technique. The aim of this delivery system is to edit a target gene in another plasmid (green fluorescent protein (GFP)). The effect of formulation and process variables were evaluated. CRISPR ALG NPs showed mean size and zeta potential of 228 nm and −4.42 mV, respectively. Over 99.0% encapsulation efficiency was achieved while preserving payload integrity. The presence of CRISPR plasmids in the ALG NPs was confirmed by Attenuated Total Reflectance-Fourier Transform Infrared Spectroscopy. The tests revealed that the nanoparticles were cytocompatible and successfully introduced the Cas9 transgene in HepG2 cells. Nanoparticles-transfected HepG2 was able to edit its target plasmid by introducing double-strand break (DSB) in GFP gene, indicating the bioactivity of CRISPR plasmids encapsulated in alginate nanoparticles. This suggests that this method is suitable for biomedical application in vitro or ex vivo. Future investigation of theses nanoparticles might result in nanocarrier suitable for in vivo delivery of CRISPR/Cas9 system.